The Effect of Inflation and Corporate Social Responsibility on Share Returns with Profitability as Intervening Variables in the Mining Sector: 2017-2019 Period - Prastyo, Verry Allan Dwi; Riyadi, Slamet; Priyawan, Sunu (International Journal of Applied Research in Management and Economics, 2021)
This study aims to prove the effect of inflation and corporate social responsibility on stock returns with profitability as an intervening variable in mining listed on the Indonesia Stock Exchange. The population of this study is 47 mining sector companies listed on the Indonesia Stock Exchange (BEI). The sampling technique uses a purposive sampling method which has certain criteria in taking samples that have an annual financial report 2017-2019, in order to obtain 22 companies. mining sector is listed on the Indonesia Stock Exchange (IDX). The method of this research uses analysis of Structural Equation Modeling (SEM) based on variance, namely Partial Least Square (PLS). SEM with variance-based PLS so that it can handle two conditions, namely conditions with undetermined factors and conditions where the solution cannot be accepted. This study uses a computer program from smart PLS 3.2 which is to determine which variables are significant to stock returns in mining listed on the Indonesia Stock Exchange for the 2017-2019 period. The results of this research show that: (1) inflation has a significant effect to stock returns; (2) inflation has a significant impact on profitability; (3) corporate social responsibility has a major impact on stock returns; (4) corporate social responsibility has a significant impact on profitability; (5) profitability has a significant impact on stock returns.